Genome-Wide Search for Competing Endogenous RNAs Responsible for the Effects Induced by Ebola Virus Replication and Transcription Using a trVLP System - Wang, Zhong-Yi; Guo, Zhen-Dong; Li, Jia-Ming; Zhao, Zong-Zheng; Fu, Ying-Ying; Zhang, Chun-Mao; Zhang, Yi; Liu, Li-Na; Qian, Jun; Liu, Lin-Na (Frontiers in Cellular and Infection Microbiology, 2017)
Understanding how infected cells respond to Ebola virus (EBOV) and how this response changes during the process of viral replication and transcription are very important for establishing effective antiviral strategies. In this study, we conducted a genome-wide screen to identify long noncoding RNAs (lncRNAs), circular RNAs (circRNAs), micro RNAs (miRNAs) and mRNAs differentially expressed during replication and transcription using a tetracistronic transcription and replication-competent virus-like particle (trVLP) system that models the life cycle of EBOV in 293T cells. To characterize the expression patterns of these differentially expressed RNAs, we performed a series cluster analysis, and up- or down-regulated genes were selected to establish a gene co-expression network. Competing endogenous RNA (ceRNA) networks based on the RNAs responsible for the effects induced by EBOV replication and transcription in human cells, including circRNAs, lncRNAs, miRNAs and mRNAs, were constructed for the first time. Based on these networks, the interaction details of circRNA-chr19 were explored. Our results demonstrated that circRNA-chr19 targeting miR-30b-3p regulated CLDN18 expression by functioning as a ceRNA. These findings may have important implications for further studies of the mechanisms of EBOV replication and transcription. These RNAs potentially have important functions and may be promising targets for EBOV therapy.